#### Answer

Answer:
(x + 3)(x - 3)

#### Work Step by Step

$x^{2} - 9$
Compare the give expression with the generalized form:
$a^{2} - b^{2}$ = (a + b)(a - b).
Here, a = x and b = 3.
Thus,
$x^{2} - 9$ = (x + 3)(x - 3)

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

Answer:
(x + 3)(x - 3)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.